RISK FACTORS OF MORTALITY IN CHILDREN WITH WILMS’ TUMOR AT SOETOMO HOSPITAL SURABAYA - Shanty, Maria Christina; Yuniarchan, Sherly; Andarsini, Mia Ratwita; Ugrasena, I Dewa Gede; Permono, Bambang; Prasetyo, Risky Vitria (Indonesian Urological Association, 2019)
Objective: Wilms’ tumor is the most common childhood renal tumor for about 6% of pediatric malignant disease. The 5-year survival rate in United States increased from approximately from 70% (1970-1973) to 92% (1989-1996). This study was aim to analyze the risk factors of mortality in children with Wilms’ tumor. Material & Methods: A cross-sectional study was conducted in children with Wilms’ tumor at Soetomo Hospital during 2006-2011. The data of demographic, clinical profile, complete blood count, blood urea nitrogen, glomerular filtration rate, histological type, disease stage, metastases and relapse were analyzed as risk factors of mortality using logistic regression. Results: There were 37 Wilms’ tumor children and 5 children were excluded because of incomplete data. The mean age was 3.0 (SD 2.6) years, and male-to-female ratio was 2.5 : 1. There were 5/32 children in stage I, 7/32 children in stage II, 8/32 children in stage III, 11/32 children in stage IV, and 1/32 children in stage V. There were 15/32 children underwent operation. Complete remission occurred in 12/32 children and 1/32 children relapsed. There were 20/32 children died, associated with anemia (P=0.033, OR=6.111, 95% CI=1.056-35.352) and advanced stage (P=0.021, OR=8.000, 95% CI=1.575-40.632). The risk of mortality increased 3.284 folds with every increased stage (P=0.007, 95% CI=1.338-7.775). Conclusion: Disease stage is the significant risk factor of mortality in children with Wilms’ tumor.